Change Is Good, But Not Too Much: Dynamic Positioning in the Interfirm Network and New Product Development. Issue 6 (24th January 2018) - Mazzola, Erica; Perrone, Giovanni; Handfield, Robert
Abstract : This research considers the dynamic positioning of an enterprise in an interfirm network and its propensity for new product development. Specifically, we explore how firms reconcile the dichotomy between central and structural holes network positions, by dynamically shifting from a central to a structural holes position (and vice versa) over time. By grounding this research in network dynamics theory, we argue how prior strong central (structural holes) network positions in the interfirm network increase the likelihood the firm will benefit from structural holes (central) positions in the following time period. We also propose that these positions can be modeled by an inverted U‐shaped relationship, which determines the firm's ability to develop new products. Indeed, by balancing central and structural holes positions, firms derive product development advantages from both network positions while reducing the relative drawbacks. However, a risk of such dynamic behavior is that when applied too often, it may prevent firms from assimilating the advantages brought by the two network positions. We test our theoretical framework with a sample of firms from the biopharmaceutical industry over a period of 10 years (2001 until 2010) using two approaches. First, we test the presence of dynamic behaviors using a panel data sample consisting of a network of 3121 firms observed for 10 years (2001–2010). Second, we explore the effect of dynamic behavior on each firm's ability to develop new products using a cross‐sectional data sample of 544 public firms belonging to the network of the 3121 firms. Our results suggest that a dynamic perspective employed in reconciling the dichotomy between central and structural holes network positions increases the ability of a firm to develop new products. However, findings also suggest that if firms shift too often from one network position to another, benefits of the dynamic network strategy are diminished.